Laser-induced incandescence in aqueous carbon black suspensions: the role of particle vaporization - Rulik, Ju.Ju.; Mikhailenko, N.M.; Zelensky, S.E.; Kolesnik, A.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
Non-linear properties and the kinetics of laser-induced incandescence in aqueous carbon black suspensions are investigated. For explanation of the observed properties, a model, which takes into account a decrease of the size of particles caused by their vaporization under laser irradiation, is proposed.